2022
DOI: 10.1177/14614448221082649
|View full text |Cite
|
Sign up to set email alerts
|

How offline backgrounds interact with digital capital

Abstract: This article investigates the interaction between digital capital and some offline components (economic, cultural, political, social and personal) that represent the background against which we access and use the Internet. Based on a stratified sample of the UK population (868), six indexes (one for each component) were generated through factor analysis and univariate analysis. We summarised them into a unique model by performing a multiple linear regression to evaluate the role-played by offline components in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 88 publications
(130 reference statements)
2
7
0
Order By: Relevance
“…Higher levels of offline resources enable better internet access and autonomy. Secondly, we tested the relationship between digital resources and digital skills, conceived as both navigational and online job-seeking skills, and found that high levels of digital resources promote high levels of digital skills (Ragnedda, 2018;Ragnedda et al, 2022;Robinson, 2009Robinson, , 2012. Hence digital resources enable the transfer of the positive benefits of existing materials, and educational resources are transferred.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher levels of offline resources enable better internet access and autonomy. Secondly, we tested the relationship between digital resources and digital skills, conceived as both navigational and online job-seeking skills, and found that high levels of digital resources promote high levels of digital skills (Ragnedda, 2018;Ragnedda et al, 2022;Robinson, 2009Robinson, , 2012. Hence digital resources enable the transfer of the positive benefits of existing materials, and educational resources are transferred.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In addition, better digital resources increase both digital proficiency and users' confidence in their ability to evaluate and filter online information (Robinson, 2009(Robinson, , 2012. The concept of "digital capital" (Ragnedda, 2018;Ragnedda et al, 2022) describes the accumulation of internet users' digital skills and resources. It represents a link between online and offline opportunities, as it can increase internet users' material resources when actioned through internet use.…”
Section: Digital Inequalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Parents' social capital is a crucial factor in this regard. As lower‐SES parents tend to have difficulty obtaining relevant social support from their surrounding environment (Ragnedda et al., 2022), they face greater emotional costs when engaging in online learning. As a result, they tend to be less accepting of online learning than higher‐SES parents.…”
Section: Discussionmentioning
confidence: 99%
“…The scientific debate also refers to additional forms of capital that contribute towards positioning digital users, such as digital capital and technocultural capital [33,34]. These concepts combine the material resources and skills necessary to navigate a technology-driven, digitally mediated social environment [35,36]. Directly connected to the notion of digital/techno capital, the concept of technological habitus has emerged as a bridge between the collective technology practices embedded in the habitus and individual actions [37,38].…”
Section: Theoretical Backgroundmentioning
confidence: 99%